A Cascade Model of Sociodevelopmental Events Leading to Men's Perpetration of Violence Against Female Romantic Partners. (October 2021) - Kaighobadi, Farnaz; Figueredo, Aurelio J.; Shackelford, Todd K.; Bjorklund, David F.
Conceptually driven by life history theory, the current study investigated a hypothesized hierarchy of behaviors leading to men's perpetration of violence in intimate relationships. Using a series of hierarchical regressions, we tested a causal cascade model on data provided by 114 men in a committed romantic relationship. The results supported the hypothesized hierarchy of sociodevelopmental events: (1) men's childhood experiences with their parents' parental effort predicted men's life history strategies; (2) men's life history strategies predicted men's behavioral self-regulation; (3) men's self-regulation predicted men's perceptions of partner infidelity risk; (4) perceptions of infidelity risk predicted men's frequency of engagement in nonviolent mate retention behaviors; (5) men's mate retention behaviors predicted men's frequency of partner-directed violence. The overall cascade model explained 36% of variance in men's partner-directed violence.